Le SCoT de l’aire métropolitaine bordelaise : de la métropole au projet intégré de territoire - Brigant, Frédéric; Giunta, Luana; Labèque, Sylvia (Scienze del Territorio, 2018)
In the territories of Bordeaux metropolitan area a transversal legal tool is available, an urban master plan known as SCoT ‘Grenelle’, which sets out a well-established intervention framework shared by all actors of local landscape. A structure, the Sysdau, is leading an implementation already started but requiring a lot more resources to let its orientations and objectives find applications and tangible translations onsite. The difference in human or financial resources between the metropolis and its neighbouring territories represents anyway a hindrance for the implementation of such dynamic. For that, the projects carried by SYSDAU propose to counterbalance metropolitan forces through an enhancement of periurban territories. All these projects are part of transition and territorial innovation. They are thus in line with the imperatives of adaptation necessary to build tomorrow’s resilient metropolises in direct contact with their natural and institutional environment.